Ecoenzymatic stoichiometry reveals phosphorus addition alleviates microbial nutrient limitation and promotes soil carbon sequestration in agricultural ecosystems - Wang, Xiangxiang; Cui, Yongxing; Wang, Yuhan; Duan, Chengjiao; Niu, Yinan; Sun, Ruxiao; Shen, Yufang; Guo, Xuetao; Fang, Linchuan (Journal of soils and sediments, 2022)
Purpose Variation in soil microbial metabolism remains highly uncertain in predicting soil carbon (C) sequestration, and is particularly and poorly understood in agroecosystem with high soil phosphorus (P) variability. Materials and methods This study quantified metabolic limitation of microbes and their association with carbon use efficiency (CUE) via extracellular enzymatic stoichiometry and biogeochemical equilibrium models in field experiment employing five inorganic P gradients (0, 75, 150, 225, and 300 kg P ha −1 ) in farmland used to grow peas. Results and discussion Results showed P fertilization significantly increased soil Olsen-P and NO 3 − -N contents, and enzyme activities (β-1,4-glucosidase and β- D -cellobiosidase) were significantly affected by P fertilization. It indicated that P fertilization significantly decreased microbial P limitation due to the increase of soil available P. Interestingly, P application also significantly decreased microbial nitrogen (N) limitation, a phenomenon primarily attributable to increasing NO 3 − -N content via increasing biological N fixation within the pea field. Furthermore, P fertilization increased microbial CUE because the reduction in microbial N and P limitation leads to higher C allocation to microbial growth. Partial least squares path modeling (PLS-PM) further revealed that the reduction of microbial metabolic limitation is conducive to soil C sequestration. Conclusions Our study revealed that P application in agroecosystem can alleviate not only microbial P limitation but also N limitation, which further reduces soil C loss via increasing microbial CUE. This study provides important insight into better understanding the mechanisms whereby fertilization mediates soil C cycling driven by microbial metabolism in agricultural ecosystems.